Anatomic Characteristics and Clinical Implications of Angiographic Coronary Thrombus. (April 2015) - Campos, Carlos M.; Costa, Francesco; Garcia-Garcia, Hector M.; Bourantas, Christos; Suwannasom, Pannipa; Valgimigli, Marco; Morel, Marie-Angele; Windecker, Stephan; Serruys, Patrick W.
<x xml:space="preserve">Abstract</x> Background— The distribution of thrombus-containing lesions (TCLs) in an all-comer population admitted with a heterogeneous clinical presentation (stable, ustable angina, or an acute coronary syndrome) and treated with percutaneous coronary intervention is yet unclear, and the long-term prognostic implications are still disputed. This study sought to assess the distribution and prognostic implications of coronary thrombus, detected by coronary angiography, in a population recruited in all-comer percutaneous coronary intervention trials. Methods and Results— Patient-level data from 3 contemporary coronary stent trials were pooled by an independent academic research organization (Cardialysis, Rotterdam, the Netherlands). Clinical outcomes in terms of major adverse cardiac events (major adverse cardiac events, a composite of death, myocardial infarction, and repeat revascularization), death, myocardial infarction, and repeated revascularization were compared between patients with and without angiographic TCL. Preprocedural TCL was present in 257 patients (5.8%) and absent in 4193 (94.2%) patients. At 3-year follow-up, there was no difference for major adverse cardiac events (25.3 versus 25.4%; P=0.683); all-cause death (7.4 versus 6.8%; P=0.683); myocardial infarction (5.8 versus 6.0%; P=0.962), and any revascularizations (17.5 versus 17.7%; P=0.822) between patients with and without TCL. The comparison of outcomes in groups weighing the jeopardized myocardial by TCL also did not show a significant difference. TCL were seen more often in the first 2 segments of the right (43.6%) and left anterior descending (36.8%) coronary arteries. The association of TCL and bifurcation lesions was present in 40.1% of the prespecified segments. Conclusions— TCL involved mainly the proximal coronary segments and did not have any effect on clinical outcomes. A more detailed thrombus burden quantification is required to investigate its prognostic implications. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifiers: NCT00114972, NCT01443104, NCT00617084.